Factors Correlated With Quality Of Patient’s Handover In Inpatient Room Of The Hospital - Sulistyawati, Wiwin; Etika, Arif Nurma; Novitasari, Restu (Journal Of Nursing Practice, 2020)
Background: Communication failure during handover is the main cause of the patient's injury and is the root cause of 65% of the sentinel incident. Bad handover is assumed to have correlation with clinical diagnosis inaccuracies, delay in diagnosis, delay in laboratory tests, treatment errors, inconsistent or misinterpretation of results, duplication of tests, increase in complications of the Hospital.Purpose: This study aimed to determine the factors related to the quality of the patient's handover in inpatient room of the hospital.Methods: This research used a correlational analysis study with a cross sectional approach. Data retrieval use questionnaires and observation sheets. The number of samples on this study is 79 nurses taken in random sampling techniques. Statistical analysis used is a test of spearman rank.Results: The result of this research revealed that most of the respondents (69.6%) are diploma graduates, and 72.2% of respondents have a working time of < 5 years. Almost all respondents (93.7%) have good motivation, and 94.9% of respondents have good handover quality. The last educational variable (p = 0.388) and the nurse’s working time (P = 0.209) are not related to the quality of the handover, while the motivation (P = 0.000) and the implementation of the chief nurse’s supervision (P = 0.000) relate to the quality of the handover between the shifts in the inpatient room of the hospital.Conclusion of this study is the motivation and the implementation of the chief nurse’s supervision relate to the quality of the handover between the shifts in the inpatient room of the hospital. Hospital’s management is expected to raise the motivation of nurses in conducting handover and enhancing the supervision of the chief nurse to improve the quality of the patient's handover and minimize the errors in information exchange conducted by nurses